Mechanisms and treatment of bone pain in multiple myeloma. Issue 4 (December 2019) - Davies, Matthew Philip; Fingas, Sam; Chantry, Andrew
Abstract : Purpose of review: Multiple myeloma is a haematological malignancy of differentiated B lymphocytes, known as plasma cells. The disease is common in the UK (incidence of 9 cases per 100 000 people) and the most frequent presentation is bone pain caused by skeletal damage. Patients with myeloma also experience neuropathic pain induced by chemotherapy. The management of pain in multiple myeloma is frequently demanding and often sub-optimally addressed. This review seeks to summarize a rational approach to the management of pain experienced by multiple myeloma patients. Recent findings: Bone pain has a dramatic detrimental impact on a patient's physical capacity, and therefore, quality of life. Various mechanisms of bone pain have been elucidated; however, neuropathic bone pain in multiple myeloma is not completely understood. Potential mechanisms for this phenomenon; namely increased intraosseous pressure and the acidity of the bone marrow in the disease state will be interrogated. The current analgesic pathways used to treat multiple myeloma bone pain and new advances in therapies that may confer future benefit to patients will briefly be reviewed. Summary: Holistic care and the provision of an array of pain relief methods is required to achieve effective pain control in multiple myeloma bone pain and requires a concerted effort from the healthcare team to be realized.